Ethnic inequalities in the use of secondary and tertiary mental health services among patients with obsessive–compulsive disorder. (December 2015) - de la Cruz, Lorena Fernández; Llorens, Marta; Jassi, Amita; Krebs, Georgina; Vidal-Ribas, Pablo; Radua, Joaquim; Hatch, Stephani L.; Bhugra, Dinesh; Heyman, Isobel; Clark, Bruce; Mataix-Cols, David
Abstract : Background: Obsessive–compulsive disorder (OCD) has similar prevalence rates across ethnic groups. However, ethnic minorities are underrepresented in clinical trials of OCD. It is unclear whether this is also the case in clinical services. Aims: To explore whether ethnic minorities with OCD are underrepresented in secondary and tertiary mental health services in the South London and Maudsley (SLaM) NHS Foundation Trust. Method: The ethnic distribution of patients with OCD seen between 1999 and 2013 in SLaM ( n = 1528) was compared with that of the general population in the catchment area using census data. A cohort of patients with depression ( n = 22 716) was used for comparative purposes. Results: Ethnic minorities with OCD were severely underrepresented across services (–57%, 95% CI –62% to –52%). The magnitude of the observed inequalities was significantly more pronounced than in depression (–29%, 95% CI–31% to–27%). Conclusions: There is a clear need to understand the reasons behind such ethnic inequalities and implement measures to reduce them.